Carbon fiber-reinforced polymer composite drilling via aluminum chromium nitride-coated tools: Hole quality and tool wear assessment. (October 2017) - Harris, Muhammad; Qureshi, Muhammad Asif Mahmood; Saleem, Muhammad Qaiser; Khan, Sarmad Ali; Bhutta, Muhammad Mahmood Aslam
Drilling into carbon fiber-reinforced polymer composites presents a stiff challenge in terms of ensuring hole quality aspects such as delamination, roughness, roundness, etc. while maintaining an adequate tool life. The hardened carbon fibers in laid up form generally give rise to chips in powdered form that contribute significantly to tool wear problem. To overcome the aforementioned issues, the use of high performance tools has been reported. This paper reports on the usage of yet another novel high performing but much economical aluminum chromium nitride-coated tools that are typically employed for metallic parts. The effect of aluminum chromium nitride tools at three spindle speeds with constant feed rate was evaluated on hole quality, tool wear, and chip formation pattern of carbon fiber-reinforced polymer composite plates. The results were compared with the performance of conventional high speed steel tools taken as baseline. It was found that the coated tools help significantly improve hole quality and provide appreciable tool life at specific machining parameters.